Characterization and Quantification of Oxidized High Mobility Group Box 1 Proteoforms Secreted from Hepatocytes by Toxic Levels of Acetaminophen - Pirnie, Ross; Gillespie, Kevin P; Weng, Liwei; Mesaros, Clementina; Blair, Ian A (Chemical research in toxicology, 2022)
The high mobility group box 1 (HMGB1), which is released during acute acetaminophen (APAP) overdose, is thought to mediate a subsequent immune response, particularly hepatic infiltration of macrophages. The redox behavior of HMGB1 and the proteoforms of HMGB1 present in oxidative environments has been the subject of a number of confusing and contradictory studies. Therefore, a stable isotope dilution two-dimensional nanoultrahigh-performance liquid chromatography parallel reaction monitoring/high-resolution mass spectrometry method was developed in order to characterize and quantify oxidative modifications to the cysteine (Cys) residues (Cys-23, Cys-45, and Cys-106) that are present in HMGB1. Disulfide linkages were determined using carbamidoethyl derivatization before and after reduction as well as by direct analysis of disulfide cross-linked peptides. A stable isotope labeled form of HMGB1 was used as an internal standard to correct for sample to sample differences in immunoaffinity precipitation, derivatization, and electrospray ionization. Four discrete HMGB1 proteoforms were found to be released from a hepatocarcinoma cell model of APAP overdose after 24 h. Fully reduced HMGB1 with all three Cys-residues in their free thiol state accounted for 18% of the secreted HMGB1. The proteoform with disulfide between Cys-23 and Cys-45 accounted for 24% of the HMGB1. No evidence was obtained for a disulfide cross-link between Cys-106 and the other two Cys-residues. However, 45% of the HMGB1 formed a cross-link with unidentified intracellular proteins via an intermolecular disulfide bond, and 12% was present as the terminally oxidized cysteic acid. Surprisingly, there was no evidence for the formation of HMGB1 disulfides with GSH or other low molecular weight thiols. Secreted plasma HMGB1 Cys-23/Cys45 disulfide proteoform together with the Cys-106/protein disulfide proteoforms could potentially serve as early biomarkers of hepatoxicity after APAP overdose as well as biomarkers of drug-induced liver injury.